What do you know off your own bat? - Hamma, Alioscia (BORNH Bulletin of Regional Natural History, 2022)
Testimony is a ubiquitous source of knowledge that has received very little attention in the history of Philosophy. The epistemology of testimony reveals the tension between realism and relativism and how morality and the theory of knowledge are connected in an inextricable way.